In vitro culture of Eucalyptus spp. : micropropagation, organogenesis, embryogenesis, cell and protoplast culture - Chang, Shu-Hwa (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.